A rare and emerging pathogen: Raoultella planticola identification based on 16S rRNA in an infant - MEMİŞOĞLU, ASLI; ÖZEK, EREN; ÜLGER, NURVER; YAKUT, NURHAYAT (ELSEVIER SCIENCE LONDON, 2018)
Raoultella planticola is rarely associated with clinical infection, and a limited number of pediatric cases have been reported. Herein we report a case of bacteremia presumptively secondary to bilateral conjunctivitis in an infant caused by R. planticola which was successfully treated with piperacillin-tazobactam. It should be kept in mind that R. planticola can be a pathogen in pediatric age groups. (C) 2017 The Authors. Published by Elsevier Limited on behalf of King Saud Bin Abdulaziz University for Health Sciences. This is an open access article under the CC BY-NC-ND license
Keywords: Infant; Conjunctivitis; Bacteremia; Raoultella; KLEBSIELLA-TREVISANII; CONJUNCTIVITIS; BACTEREMIA; INFECTION; NOV